Sunyaev–Zel'dovich effect and X-ray scaling relations from weak lensing mass calibration of 32 South Pole Telescope selected galaxy clusters. Issue 3 (20th December 2018) - Dietrich, J P; Bocquet, S; Schrabback, T; Applegate, D; Hoekstra, H; Grandis, S; Mohr, J J; Allen, S W; Bayliss, M B; Benson, B A; Bleem, L E; Brodwin, M; et al.
Abstract: Uncertainty in mass–observable scaling relations is currently the limiting factor for galaxy-cluster-based cosmology. Weak gravitational lensing can provide direct mass calibration and reduce the mass uncertainty. We present new ground-based weak lensing observations of 19 South Pole Telescope (SPT) selected clusters at redshifts 0.29 ≤ z ≤ 0.61 and combine them with previously reported space-based observations of 13 galaxy clusters at redshifts 0.576 ≤ z ≤ 1.132 to constrain the cluster mass scaling relations with the Sunyaev–Zel'dovich effect (SZE), the cluster gas mass M gas and Y X, the product of M gas and X-ray temperature. We extend a previously used framework for the analysis of scaling relations and cosmological constraints obtained from SPT-selected clusters to make use of weak lensing information. We introduce a new approach to estimate the effective average redshift distribution of background galaxies and quantify a number of systematic errors affecting the weak lensing modelling. These errors include a calibration of the bias incurred by fitting a Navarro–Frenk–White profile to the reduced shear using N -body simulations. We blind the analysis to avoid confirmation bias. We are able to limit the systematic uncertainties to 5.6% in cluster mass (68% confidence). Our constraints on the mass–X-ray observable scaling relation parameters are consistent with those obtained by earlier studies and our constraints for the mass–SZE scaling relation are consistent with the simulation-based prior used in the most recent SPT–SZ cosmology analysis. We can now replace the external mass calibration priors used in previous SPT–SZ cosmology studies with a direct, internal calibration obtained for the same clusters.